1997
DOI: 10.1002/(sici)1098-1098(1997)8:6<572::aid-ima10>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional, physiological, and metabolic toolbox for clinical magnetic resonance imaging: Integration of acquisition and analysis strategies

Abstract: Selected neuroimaging strategies have been integrated into a clinical brain imaging protocol to provide quantitative high‐resolution functional, physiological, and metabolic maps to complement exquisitely detailed anatomic images without excessively prolonging the conventional clinical examination or analysis time. The physiological maps of blood pool parameters (relative cerebral blood volume, tissue transit time, and arrival time), apparent diffusion coefficient, tissue water content, and functional neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Our experience is that such interference from the visual feedback system is not significant in the activation maps produced with t-tests at either 1.5 or 3.0 T. The visor reduces head motion for cooperative subjects to allow whole-brain fMRI. This is suitable for mapping studies as used clinically for locating eloquent cortex in presurgical planning for epilepsy (27,28). Given the requirement to minimize head motion, the current device fills an important role in aiding the acquisition of high-quality fMRI data without patient discomfort from bite bar or thermoplastic mask.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience is that such interference from the visual feedback system is not significant in the activation maps produced with t-tests at either 1.5 or 3.0 T. The visor reduces head motion for cooperative subjects to allow whole-brain fMRI. This is suitable for mapping studies as used clinically for locating eloquent cortex in presurgical planning for epilepsy (27,28). Given the requirement to minimize head motion, the current device fills an important role in aiding the acquisition of high-quality fMRI data without patient discomfort from bite bar or thermoplastic mask.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used in the aforementioned studies are only able to provide a weighted average of the intracellular and extracellular signals. However, measurement of the changes in sodium concentration in the intracellular compartment would yield useful information on cell viability (2, 6). A number of previous studies showed different ways to differentiate intracellular from extracellular sodium signals.…”
Section: Introductionmentioning
confidence: 99%
“…The signal originating from the intracellular space is particularly interesting when assessing cell viability. 9,10 As suggested by previous findings, the TQ signal might be sensitive to the intracellular compartment 8,[11][12][13] and therefore, possibly enables additional tissue characterization. Sampling MQCs is challenging and requires specific 23 Na MR sequences involving at least three radiofrequency (RF) pulses with multiple phase-cycling to filter for the 23 Na quantum coherences.…”
Section: Introductionmentioning
confidence: 67%
“…Especially the triple quantum (TQ) signal could provide richer tissue sodium characterization, which is linked to cell vitality 7,8 when compared to conventional single quantum (SQ) signal alone. The signal originating from the intracellular space is particularly interesting when assessing cell viability 9,10 . As suggested by previous findings, the TQ signal might be sensitive to the intracellular compartment 8,11–13 and therefore, possibly enables additional tissue characterization.…”
Section: Introductionmentioning
confidence: 92%